DEVELOPMENT OF A MULTI-REPRESENTATION-BASED PHYSICS TEACHING MODULE TO IMPROVE STUDENTS' ANALYTICAL THINKING SKILLS ON RECTILINEAR MOTION - Dwi Setiawati; Helmi; Kaharuddin Arafah (SOSIOEDUKASI, 2026)
Twenty-first-century learning requires students to master analytical thinking, one of the higher-order thinking skills needed to identify information, connect concepts, interpret data, and draw evidence-based conclusions. In physics learning, rectilinear motion is a fundamental topic that requires students to integrate verbal, mathematical, graphical, and pictorial representations, an ability known as multi-representation competence. This study aimed to develop a multi-representation-based physics teaching module to improve students' analytical thinking skills on the topic of rectilinear motion and to determine its content validity and practicality. This research and development (R&D) study used the 4D model (Define, Design, Develop, Disseminate) developed by Thiagarajan et al. (1974). The trial subjects were students of class X.1 at SMA Negeri 2 Makassar. Data were collected through expert validation sheets and teacher and student response questionnaires and were analyzed using Aiken's V content validity index and the practicality percentage (PRS) formula. The results showed that the multi-representation-based physics teaching module obtained an average Aiken's V index of 0.924, categorized as valid, while the supporting research instruments obtained an average Aiken's V of 0.80, also categorized as valid. The teacher response questionnaire showed an average practicality percentage of 86.1%, categorized as very practical. These findings indicate that the developed module is valid and very practical for supporting physics learning on the rectilinear motion topic and for training students' analytical thinking skills.